Pengaruh Pelatihan, Motivasi, Dan Lingkungan Kerja Terhadap Produktivitas Kerja Pegawai Negeri Sipil (PNS) Pada Dinas Pariwisata Kota Batu - Kamilla, Nahya Izza; Nurhidayah, Nurhidayah; Novianto, Abdullah Syakur (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research aims to determine the influence of Training, Motivation and Work Environment on the Work Productivity of Civil Servants (PNS) at the Batu City Tourism Office. This research uses non-probability sampling with saturated sampling (census) so that 58 respondents can be determined. This research uses a quantitative approach with data processing analysis using IBM SPSS Statistics 25 for Windows. The findings of this research are that training has a significant positive effect on the productivity of Civil Servants (PNS) of the Batu City Tourism Office, Motivation has a significant negative effect on the Productivity of Civil Servants (PNS) of the Batu City Tourism Department, and the work environment has a significant positive effect on the Productivity of Civil Servants Civil (PNS) Batu City Tourism Department. Keywords: Training, Motivation, Work Environment, and Work Productivity